Efecto de la velocidad rotacional en reactor biodiscos sobre la remoción de materia orgánica en un agua residual doméstica de campamento Minero la Libertad - Perú - Vásquez Salazar, Edgar Enrique (2018)
ABSTRACT This research looked for to evaluate the effect of rotational velocity in a rotating biological contactor on the organic matter removal in sewage from a mining camp at the Libertad region, Perú. The experiment used a randomized block design with three replications. Treatments consisted in four rotating velocities (1 RPM, 2 RPM, 3 RPM, y 4 RPM). At rotating velocities: 1 RPM, 2 RPM, and 4 RPM (48.19 mg/L DBO5, 37.06 mg/L DBO5, and 46.98 mg/L DBO5, average organic matter obtained from tests in blocks), did not get good organic matter removal efficiency, due to a lack oxygen levels for biomass growth at rotating velocities 1 RPM and 2 RPM; and biomass sloughing at 4 RPM rotating velocity. However, at 3 RPM rotating velocity, results revealed the best biodegradable organic matter removal efficiency: 94.95%, suitable to oxygenation profile through the reactor. Test results in three blocks; determined that most appropriated rotating velocity was 3 RPM, with an average organic matter content of 19.15 mg DBO5/L. It was demonstrated that rotating velocity is an important factor that affect rotating biological contactor performance and the effluent quality.